2021
DOI: 10.1016/j.stemcr.2020.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy of Dominant CRX-Leber Congenital Amaurosis using Patient Stem Cell-Derived Retinal Organoids

Abstract: Summary Mutations in the photoreceptor transcription factor gene cone-rod homeobox (CRX) lead to distinct retinopathy phenotypes, including early-onset vision impairment in dominant Leber congenital amaurosis (LCA). Using induced pluripotent stem cells (iPSCs) from a patient with CRX -I138fs48 mutation, we established an in vitro model of CRX -LCA in retinal organoids that showed defective photoreceptor maturation by histology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 31 publications
(45 reference statements)
2
59
0
Order By: Relevance
“…Previous reports indicated the feasibility and validity of this approach, comparing AAV transduction efficacy on stem cell-derived RPE and photoreceptors ( Gonzalez-Cordero et al., 2018 ) and analyzing mechanisms of cell attachment and their interplay with primary cell-surface receptors ( Garita-Hernandez et al., 2020 ). AAVs were even successfully used to correct congenital retinopathy phenotypes in patient stem cell-derived ROs ( Kruczek et al., 2021 ). Here, we further extended this concept by an in-depth analysis of various capsids linked to retinal gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated the feasibility and validity of this approach, comparing AAV transduction efficacy on stem cell-derived RPE and photoreceptors ( Gonzalez-Cordero et al., 2018 ) and analyzing mechanisms of cell attachment and their interplay with primary cell-surface receptors ( Garita-Hernandez et al., 2020 ). AAVs were even successfully used to correct congenital retinopathy phenotypes in patient stem cell-derived ROs ( Kruczek et al., 2021 ). Here, we further extended this concept by an in-depth analysis of various capsids linked to retinal gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A further investment that would prove beneficial to the study of disease and treatment options for STGD1, STGD3 and STGD4 is the generation of retinal organoids from patient samples. After first generating iPSCs, differentiation into retinal organoids (an additional timeframe of 120-280 days depending on the degree of maturation desired) can provide evidence of disease phenotype, as has been seen with other such models for inherited retinal disease [42][43][44][45][46][47][48][49], and then provide an opportunity for correction of phenotype following treatment [42,45,48].…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…The existing animal models do not fully reproduce the complexities of the human disease, and a lack of translatability could be hindering the development of new therapies. A study by Kruczek et al 1 reported the creation of an in vitro model of LCA based on patient-derived induced pluripotent stem cells (iPSCs). Many forms of LCA are associated with dominant mutations in the cone-rod homeobox protein CRX, which is essential for the development of photoreceptors in the retina.…”
Section: Gene Therapy-based Treatment Tested On Retinal Organoidsmentioning
confidence: 99%